Investigating fracture initiation and propagation in deep buried shale due to thermal shock: a numerical approach - Wang, Wei; Zhao, Peng; Liao, Yisha; Zhang, Yuelei; Peng, Jiao; Xian, Hongyu; Liu, Jun (Frontiers in Energy Research, 2023)
As the burial depth of shale exploitation increases, it is challenge to form fracture networks through hydraulic fracturing technology. When cryogenic fluid contacts with hot rock, heat exchange process occurs and temperature gradient is generated at the rock surface, resulting in thermal stress. Once the thermal stress exceeds the tensile strength, the fractures are generated. To study the initiation and propagation of fractures induced by thermal shock, a thermal-mechanical (TM) coupled two-dimensional model is developed in the paper. To simulate the heat exchange process, the heat convective boundary is applied in the surface between the fluid and the rock. In addition, the initiation and propagation of fractures are described by the cohesive zone model. The accuracy and reliability of the numerical model is validated by an existing analytical solution. Under the thermal shock, the temperature at the contact surface drops quickly. The stress distribution is determined by the temperature variation. The variations of temperature and stress are greatly affected by the heat exchange coefficient. With the fractures embedded in the model, the initiation and propagation of fractures are analysed. The multi-fracture propagation induced by thermal shock exhibits competition effect. With the propagation of fractures, the stress distribution in the rock changes. The heat exchange coefficient has a significant effect on fracture initiation and propagation, presenting more fractures generation in the larger coefficient.